Apoptosis of hepatic stellate cells: involvement in resolution of biliary fibrosis and regulation by soluble growth factors. Issue 4 (1st April 2001) - Issa, R; Williams, E; Trim, N; Kendall, T; Arthur, M J P; Reichen, J; Benyon, R C; Iredale, J P
Abstract : BACKGROUND: Activated hepatic stellate cells (HSC) are central to the pathogenesis of liver fibrosis, both as a source of fibrillar collagens that characterise fibrosis and matrix degrading metalloproteinases and their tissue inhibitors, the TIMPs. AIMS: To test the hypothesis that HSC apoptosis is critical to recovery from biliary fibrosis and that soluble growth factors may regulate HSC survival and apoptosis. METHODS: Rats (n=15) were subjected to bile duct ligation for 21 days, after which biliodigestive anastomosis was undertaken (n=13). Livers were harvested at fixed time points of recovery for periods of up to 42 days. Numbers of activated HSCs were quantified after α smooth muscle actin staining and HSC apoptosis was detected by terminal UDP-nick end labelling (TUNEL) staining and quantified at each time point. HSC apoptosis was quantified in vitro in the presence or absence of insulin-like growth factor (IGF)-1, IGF-2, platelet derived growth factor (PDGF), and transforming growth factor β1 (TGF-β1 ). RESULTS: Following biliodigestive anastomosis after 21 days of bile duct ligation, rat liver demonstrated a progressive resolution of biliary fibrosis over 42 days, associated with a fivefold decrease in activated HSC determined by α smooth muscle actin staining. TUNEL staining indicated that loss of activated HSC resulted from an increase in the rate of apoptosis during the first two days post biliodigestive anastomosis. Serum deprivation and culture in the presence of 50 μM cycloheximide was associated with an increase in HSC apoptosis which was significantly inhibited by addition of 10 ng/ml and 100 ng/ml IGF-1, respectively (0.05>p, n=5). In contrast, 1 and 10 ng/ml of TGF-β1 caused a significant increase in HSC apoptosis compared with serum free controls (p<0.05, n=4). PDGF and IGF-2 were neutral with respect to their effect on HSC apoptosis. CONCLUSION: HSC apoptosis plays a critical role in the spontaneous recovery from biliary fibrosis. Both survival and apoptosis of HSC are regulated by growth factors expressed during fibrotic liver injury.